Effect of feed additive supplementation on rumen bacterial amino acid profile and fermentation dynamics in dairy cows - Erasmus, L.J. (Lourens Jacobus) (University of Pretoria, 2019)
Dissertation (MSc (Agric))--University of Pretoria, 2019.